PENGGUNAAN PROTEASE DARI GETAH BIDURI DALAM PRODUKSI FLAVOR UDANG WINDU (PENAEUS MONODON) - Hardi, Jaya; Diharnaini, Diharnaini (Univ. Tadulako, 2014)
Shrimp flavor including one of the high-value product that can be produced from the sap biduri protease activity. This research intends to know the concentration of biduri protease isolated and reaction times that result high-quality shrimp flavor. Achievement of objectives has been applied randomized block design with factorial treatment pattern that consists of two factors, namely the biduri protease concentration factor with three levels and hydrolysis time factor with three levels. Observed parameters include water content, soluble protein content and organoleptic quality of shrimp flavor. The results obtained indicate the concentration of biduri protease having an affect on the water content, soluble protein content and organoleptic quality, while the hydrolysis time having an affect only on the soluble protein content and organoleptic quality. The highest soluble protein content (71.65%) and the lowest water content (11.08%) was found in the combination of biduri protease concentration of 2.5% for 2 hours hydrolysis.